Usefulness of the capsule endoscopy Crohn's disease activity index in assessing the necessity of early additional treatment in patients with Crohn's disease in clinical remission. Issue 29 (23rd July 2021) - Miyazu, Takahiro; Ishida, Natsuki; Takano, Ryosuke; Tamura, Satoshi; Yamade, Mihoko; Hamaya, Yasushi; Tani, Shinya; Iwaizumi, Moriya; Osawa, Satoshi; Furuta, Takahisa; Sugimoto, Ken
Abstract : Abstract: The Capsule Endoscopy Crohn's Disease Activity Index (CECDAI) was recently reported as a new scoring system to evaluate the mucosal lesions of patients with Crohn's disease (CD). We investigated whether CECDAI is useful for assessing the necessity of early additional treatment in patients with CD in clinical remission. Twenty-one patients with small intestinal CD in clinical remission underwent capsule endoscopy (CE). The CECDAI and Lewis score (LS) were used to evaluate the intestinal lesions. We analyzed the correlations between several biomarkers and CECDAI or LS and examined the changes in therapeutic regimens based on the CECDAI. CE identified intestinal abnormalities in most CD patients in clinical remission: 81.0% and 85.7%, as assessed using CECDAI and LS, respectively. A significant positive correlation was observed between the CDAI and LS ( P  = .025), as well as between CDAI and CECDAI ( P  = .014) in these cases. Compared to LS, CECDAI scores were more evenly distributed. No significant correlations were observed between endoscopic scores and serum markers, including CRP, hemoglobin, and albumin levels. Additional treatment was performed significantly more often in patients with moderate-severe disease activity (CECDAI ≥5.8) ( P  = .012) than in those with normal (CECDAI <3.5) and mild (3.5⩽CECDAI<5.8) disease activity. Resection of the small intestine did not affect the small bowel transit time or CE score. CECDAI is useful in evaluating mucosal lesions in small bowel CD patients in clinical remission and helps in assessing the requirement for additional treatment for these patients, including those who undergo intestinal resection. Abstract : Supplemental Digital Content is available in the text